Risks of passive use of social network sites in youth athletes: a moderated mediation analysis - Zhang, Weipeng; Jiang, Feng; Zhu, Yuanjiao; Zhang, Qiang (Frontiers in Psychology, 2023)
Background With the popularity of social media platforms, the use of social networks challenges the well-being and mental health of athletes. Motivation Despite ongoing scholarly discussions about the effects of passive use of social network sites, few studies have examined the relationship between the passive use of social network sites and mental health in young athletes from a social comparison perspective. Hypothesis To address this research gap, we draw on the social comparison and developmental systems theories to explore the mediating effect of upward social comparison on passive social network site use and mental health, as well as the moderating effects of positive psychological capital. Methods We analyzed data about 350 young athletes from professional Chinese sports universities. Results As predicted, passive use of social network sites by young athletes increased anxiety (β = 0.26, p < 0.001) and decreased subjective well-being (β = −0.35, p < 0.001). Upward social comparisons had positive (β = 0.22, p < 0.001) and negative (β = −0.34, p < 0.001) mediating effects in passive social network site use and anxiety/subjective well-being. Positive psychological capital played a moderating effect between upward social comparison and anxiety (β = −0.28, p < 0.001), and subjective well-being (β = 0.24, p < 0.001); the moderated mediation effect was also supported. Conclusion Our study informs the current research by highlighting the importance of upward social comparison as a critical mechanism and positive psychological capital as a boundary condition. We suggest actively maintaining and enhancing positive psychological capital to mitigate the adverse effects of upward social comparison.